Antimicrobial activity of iron-depriving pyoverdines against human opportunistic pathogens - Vera Vollenweider; Karoline Rehm; Clara Chepkirui; Manuela Pérez-Berlanga; Magdalini Polymenidou; Jörn Piel; Laurent Bigler; Rolf Kümmerli (eLife)
The global rise of antibiotic resistance calls for new drugs against bacterial pathogens. A common approach is to search for natural compounds deployed by microbes to inhibit competitors. Here, we show that the iron-chelating pyoverdines, siderophores produced by environmental Pseudomonas spp., have strong antibacterial properties by inducing iron starvation and growth arrest in pathogens. A screen of 320 natural Pseudomonas isolates used against 12 human pathogens uncovered several pyoverdines with particularly high antibacterial properties and distinct chemical characteristics. The most potent pyoverdine effectively reduced growth of the pathogens Acinetobacter baumannii, Klebsiella pneumoniae, and Staphylococcus aureus in a concentration- and iron-dependent manner. Pyoverdine increased survival of infected Galleria mellonella host larvae and showed low toxicity for the host, mammalian cell lines, and erythrocytes. Furthermore, experimental evolution of pathogens combined with whole-genome sequencing revealed limited resistance evolution compared to an antibiotic. Thus, pyoverdines from environmental strains have the potential to become a new class of sustainable antibacterials against specific human pathogens.